TEACHING SEMANTICS TO EFL STUDENTS VIA MOBILE ASSISTED DEVICES - Ganieva Saodat Abduxafizovna. (International Journal of Innovations in Engineering Research and Technology, 2021)
This article highlights the method of teaching semantics in the example of video material. It gives definition and examples of semantics. Teachers of English as a foreign language can make use of the lesson plan of how to teach semantics to efl students through the video material and the tasks, and a quiz.